2021
DOI: 10.3390/jpm11090880
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Features of Rem Sleep Behaviour Disorder

Abstract: Dopaminergic deficiency, shown by many studies using functional neuroimaging with Single Photon Emission Computerized Tomography (SPECT) and Positron Emission Tomography (PET), is the most consistent neurochemical feature of rapid eye movement (REM) sleep behaviour disorder (RBD) and, together with transcranial ultrasonography, and determination of alpha-synuclein in certain tissues, should be considered as a reliable marker for the phenoconversion of idiopathic RBD (iRBD) to a synucleopathy (Parkinson’s disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 194 publications
(374 reference statements)
0
9
0
Order By: Relevance
“…Given the facts that PD is a very common neurological disorder and RBD is frequently associated with it before the onset of motor symptoms, it seems reasonable studies looking for neuroprotective strategies should include a selection of patients with polysomonographically confirmed iRBD and neurochemical and/or neuroimaging markers that suggest a high-risk of phenoconversion to synucleinopathies [15,91,97,99]. The combination of functional neuroimaging studies using different tracers, transcranial sonography, brain per-fusion and glucose metabolism studies, functional MRI, and the detection of α-synuclein in certain tissues should be useful for this purpose [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the facts that PD is a very common neurological disorder and RBD is frequently associated with it before the onset of motor symptoms, it seems reasonable studies looking for neuroprotective strategies should include a selection of patients with polysomonographically confirmed iRBD and neurochemical and/or neuroimaging markers that suggest a high-risk of phenoconversion to synucleinopathies [15,91,97,99]. The combination of functional neuroimaging studies using different tracers, transcranial sonography, brain per-fusion and glucose metabolism studies, functional MRI, and the detection of α-synuclein in certain tissues should be useful for this purpose [15].…”
Section: Discussionmentioning
confidence: 99%
“…The neurochemical features of RBD include dopaminergic deficiency (the most consistent finding) and changes in noradrenaline, acetylcholine, excitatory and inhibitory neurotransmitters, hormones such as melatonin, and proinflammatory factors [15]. Patterns resembling those of PD and/or LBD have been found in brain glucose metabolism and brain perfusion studies, and cortical grey matter atrophy, structural changes in deep grey matter nuclei, and alterations in the functional connectivity between several networks including the basal ganglia and cerebral cortex have been found by using structural and functional MRI [15].…”
Section: Introductionmentioning
confidence: 92%
“… 19 Furthermore, there is also evidence showing that psychological stress itself, regardless of PTSD, provokes disturbances of noradrenergic function in various brain regions. 20 Given the potential role of noradrenaline in the occurrence of RBD, 21 one can postulate that noradrenergic pathway alterations due to emotional stress contribute to the aggravation of DEBs in iRBD patients. Although stress has also been reported to increase serotonin turnover in the brain, 22 it remains debatable whether the serotonergic system is directly involved in RBD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that REM behaviour disorder is a very infrequent condition in children, 44 Trajanovic et al 45 described a boy diagnosed with TS who developed a clinical picture compatible with this disease aged 7 years. Modafferi et al 37 reported a frequency of 5.6% of sleep paralysis in patients with tic disorders and 2.6% in controls, although the difference did not reach statistical significance.…”
Section: Association Between Specific Sleep Disorders and Tourette Sy...mentioning
confidence: 99%